Depletion of BBS Protein LZTFL1 Affects Growth and Causes Retinal Degeneration in Mice. (20th June 2016) - Jiang, Jiangsong; Promchan, Kanyarat; Jiang, Hong; Awasthi, Parirokh; Marshall, Heather; Harned, Adam; Natarajan, Ven
Abstract: Bardet-Biedl syndrome (BBS) is a heterogeneous disease characterized by deficiencies in various organs that are caused by defects in genes involved in the genesis, structural maintenance, and protein trafficking of cilia. Leucine zipper transcription factor-like 1 (LZTFL1) has been identified as a BBS protein (BBS17), because patients with mutations in this gene exhibit the common BBS phenotypes. In this study, we generated a knockout mouse model to investigate the effects of LZTFL1 depletion. Lztfl1 knockout mice were born with low birth weight, reached similar weight to those of wild-type mice at 10 weeks of age, and later gained more weight than their wild-type counterparts. LZTFL1 was localized to the primary cilium of kidney cells, and the absence of LZTFL1 increased the ciliary localization of BBS9. Moreover, in the retinas of Lztfl1 knockout mice, the photoreceptor outer segment was shortened, the distal axoneme of photoreceptor connecting cilium was significantly enlarged, and rhodopsin was targeted to the outer nuclear layer. TUNEL assay showed that many of these abnormal photoreceptor cells in Lztfl1 knockout mice underwent apoptosis. Interestingly, the absence of LZTFL1 caused an abnormal increase of the adaptor protein complex 1 (AP1) in some photoreceptor cells. Based on these data, we conclude that LZTFL1 is a cilium protein and regulates animal weight and photoreceptor connecting cilium function probably by controlling microtubule assembly and protein trafficking in cilia.